Prinsip Dasar Penyelengaraan Pendidikan dan Pohon Keilmuan Pendidikan Dasar - Pratiwi, Emy Yunita Rahma; Dwinata, Anggara (Jurnal Simki Pedagogia, 2023)
In this article, we will discuss the basic principles of education and basic scientific trees. With the aim of research to find out and as additional references relating to the basic principles of education. The research method used is descriptive quantitative with the process of giving questionnaires to teachers regarding the four principles to explore how their perspectives will form the scientific tree and its urgency. The results state that all principles are important to note because they affect the way the teacher thinks and behaves during learning. The position of the scientific tree itself is the main basis for teachers to think and act to achieve learning success. For this reason, these principles are the roots that underlie strengthening what teachers and gentlemen will do in the future. For this reason, the teacher's activities that adapt the sociological, anthropological and psychological philosophical principles must really be considered because it will affect the success of the educational process they are carrying out.